A heuristic to minimize the inventory value of repairable parts with service constraints: Application to an airline company - Manuel Cardós; Eugenia Babiloni; Marta Elena Palmer Gato; Ester Guijarro (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: This paper focuses on the improvement of the inventory management of repairable parts of the airline company Air Nostrum. The company uses a common sales replacement policy to manage their repairable parts and the same target fill rate for every item. This target is very high in order to assure a high availability of the aircrafts, dealing also to a high inventory value. Design/methodology/approach: However, this paper shows that an alternative heuristic approach outperforms the previous one terms of inventory value while fulfilling the target fill rate. Findings and Originality/value: This improvement is illustrated with an extensive and real dataset and may lead to a significant inventory reduction. Originality/value: Therefore, a company can design its inventory policies applying this heuristic focused on inventory reduction with a service level constraint instead of the usual cost optimization or service level fulfillment.
Keywords: 650; inventory management; airline industry; ABC classification